2019
DOI: 10.1371/journal.pone.0210205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior capsule polish on visual function: A meta-analysis

Abstract: PurposeTo investigate the relationship between anterior capsule polish and visual function.MethodsData were obtained from Pubmed, Embase, Web of Science, WanFang, VIP and CNKI up to the end of May 2018, without any date or language restrictions for trials. The modified Jadad scale and the newcastle-ottawa scale were used to assess the quality of included studies. Uncorrected visual acuity (UCVA) and posterior capsule opacification (PCO) were used as outcome variables. Data on anterior capsule polish were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the past two decades, the use of ACP to prevent PCO after uneventful phacoemulsification has been a frequent topic of discussion and research among cataract surgeons worldwide (8)(9)(10)(11)(12). Nevertheless, no consensus has been reached on the efficacy of polishing.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, the use of ACP to prevent PCO after uneventful phacoemulsification has been a frequent topic of discussion and research among cataract surgeons worldwide (8)(9)(10)(11)(12). Nevertheless, no consensus has been reached on the efficacy of polishing.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the results posited that lower anterior capsule opaci cation (ACO) and brotic PCO with both round-edged silicone IOLs 3-years postoperatively in eyes which the anterior capsule was extensively polished [16] . A meta-analysis of studies for 1-year or longer follow-up showed that the PCO rate was reduced in the ACP group based on the summary odds ratio on the PCO rate (OR 0.42 95% CI 0.24-0.73) [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Posterior capsule opacification (PCO) develops regularly after cataract surgery [1]. This unwanted wound healing reaction is thought to originate from lens epithelial cells that remain in the capsular bag after cataract surgery, especially on the inside of the anterior capsule and the capsular equator.…”
Section: Introductionmentioning
confidence: 99%